Blind recognition of BCH codes in faster‐than‐Nyquist signalling system. Issue 9 (11th April 2016) - Wu, Gang; Zhang, Bangning; Guo, Daoxing; Liang, Xiaohu
Abstract : Proposed is a blind recognition method for Bose–Chaudhuri–Hocquenghem (BCH) codes in the faster‐than‐Nyquist (FTN) signalling system which is based on the Galois field Fourier transform of the code polynomial. Considering the signal‐to‐noise ratio estimation in coloured noise, the proposed method can maximise the correct recognition probability of the roots of the generator polynomial by an appropriate decision criterion. Moreover, an optimal threshold of the decision criterion is deduced. Simulation results demonstrate that the proposed method can recognise the BCH codes efficiently in the FTN signalling system.